Heterogeneous reaction of ClONO2 with TiO2 and SiO2 aerosol particles: implications for stratospheric particle injection for climate engineering - M. Tang (Atmospheric Chemistry and Physics, 2016)
Deliberate injection of aerosol particles into the stratosphere is a potential climate engineering scheme. Particles injected into the stratosphere would scatter solar radiation back to space, thereby reducing the temperature at the Earth's surface and hence the impacts of global warming. Minerals such as TiO2 or SiO2 are among the potentially suitable aerosol materials for stratospheric particle injection due to their greater light-scattering ability than stratospheric sulfuric acid particles. However, the heterogeneous reactivity of mineral particles towards trace gases important for stratospheric chemistry largely remains unknown, precluding reliable assessment of their impacts on stratospheric ozone, which is of key environmental significance. In this work we have investigated for the first time the heterogeneous hydrolysis of ClONO2 on TiO2 and SiO2 aerosol particles at room temperature and at different relative humidities (RHs), using an aerosol flow tube. The uptake coefficient, γ(ClONO2), on TiO2 was ∼ 1.2 × 10−3 at 7 % RH and remained unchanged at 33 % RH, and increased for SiO2 from ∼ 2 × 10−4 at 7 % RH to ∼ 5 × 10−4 at 35 % RH, reaching a value of ∼ 6 × 10−4 at 59 % RH. We have also examined the impacts of a hypothetical TiO2 injection on stratospheric chemistry using the UKCA (United Kingdom Chemistry and Aerosol) chemistry–climate model, in which heterogeneous hydrolysis of N2O5 and ClONO2 on TiO2 particles is considered. A TiO2 injection scenario with a solar-radiation scattering effect very similar to the eruption of Mt Pinatubo was constructed. It is found that, compared to the eruption of Mt Pinatubo, TiO2 injection causes less ClOx activation and less ozone destruction in the lowermost stratosphere, while reduced depletion of N2O5 and NOx in the middle stratosphere results in decreased ozone levels. Overall, no significant difference in the vertically integrated ozone abundances is found between TiO2 injection and the eruption of Mt Pinatubo. Future work required to further assess the impacts of TiO2 injection on stratospheric chemistry is also discussed.